Ascorbic Acid Chemosensitizes Colorectal Cancer Cells and Synergistically Inhibits Tumor Growth - Pires, Ana S.; Marques, Cláudia R.; Encarnação, João C.; Abrantes, Ana M.; Marques, Inês A.; Laranjo, Mafalda; Oliveira, Rui; Casalta-Lopes, João E.; Gonçalves, Ana C.; Sarmento-Ribeiro, Ana B.; Botelho, Maria F. (Frontiers in Physiology, 2018)
Colorectal cancer (CRC) is continuously classified as one of the most incident and mortal worldwide. The positive outcomes of the conventional chemotherapy are frequently associated with high toxicity, which often leads to the suspension of the treatment. Growing evidences consider the use of pharmacological concentrations of ascorbic acid (AA), better known as vitamin C, in the treatment of cancer. The use of AA in a clinical context is essentially related to the adoption of new therapeutic strategies based on combination regimens, where AA plays a chemosensitizing role. The reduced sensitivity of some tumors to chemotherapy and the highly associated adverse effects continue to be some of the major obstacles in the effective treatment of CRC. So, this paper aimed to study the potential of a new therapeutic approach against this neoplasia with diminished side effects for the patient. This approach was based on the study of the combination of high concentrations of AA with reduced concentrations of drugs conventionally used in CRC patients and eligible for first and second line chemotherapeutic regimens, namely 5-fluorouracilo (5-FU), oxaliplatin (Oxa) or irinotecan (Iri). The evaluation of the potential synergy between the compounds was first assessed in vitro in three CRC cell lines with different genetic background and later in vivo using one xenograft animal model of CRC. AA and 5-FU act synergistically in vitro just for longer incubation times, however, in vivo showed no benefit compared to 5-FU alone. In contrast to the lack of synergy seen in in vitro studies with the combination of AA with irinotecan, the animal model revealed the therapeutic potential of this combination. AA also potentiated the effect of oxaliplatin, since a synergistic effect was demonstrated, in almost all conditions and in the three cell lines. Moreover, this combined therapy caused a stagnation of the tumor growth rate, being the most promising tested combination. Pharmacological concentrations of AA increased the efficacy of irinotecan and oxaliplatin against CRC, with promising results in cell lines with more aggressive phenotypes, namely, tumors with mutant or null P53 expression and tumors resistant to chemotherapy.